Conceptual framework for management or transmission of knowledge in companies: A systematic review - Pereira, Cláudia; Delgoulet, Catherine; Santos, Marta (Frontiers in Psychology, 2023)
The literature on knowledge management as a broad area typically studied under the scope of business management and on knowledge transmission as a process often studied under the scope of work psychology and ergonomics, although extensive, lacks a synthesis about the dimensions involved in the knowledge management or transmission practices in workplaces. Thus, the study aims to systematise the existing programs for management or transmission of knowledge in workplaces and to develop a conceptual framework to support their design and implementation in workplaces. Thereto, the study resorts to the main scientific approaches that address knowledge management and knowledge transmission (business management and work psychology/ergonomics). The methodology followed a systematic review to identify and analyse the programs for management or transmission of knowledge implemented in professional contexts, nearly from the beginning of the 21st century, considering the two scientific approaches. The analysis of the 28 articles shows what defines the implemented practices, their impacts, and the role HR assumes in it. The results demonstrate differences and similarities between the two approaches, which guided the dimensions included in the conceptual framework. This study makes advances for the scientific field bringing different scientific discourses closer together considering its strengths; and for practitioners through the possibility of advancing the understanding of the scope of application of the concepts of knowledge management and knowledge transmission and supporting their action in workplaces.